Assessing Mobility-Driven Socio-Economic Impacts on Quality of Life in Small Urban Areas: A Case Study of the Great Belt Fixed Link Corridor - Irma Kveladze; Rie Friberg Lund; Sisse Holmsted Kjeller (Urban Science, 2025)
Mobility is a fundamental catalyst for urban transformation, particularly in smaller urban centres, where enhanced transport can significantly influence socio-economic dynamics. This study investigates the socio-economic and spatial developments associated with the fixed-link transport corridor connecting the Zealand and Funen islands in Denmark. Despite its importance, a gap remains in understanding how this transport corridor has reshaped inter-regional connectivity over three decades and affected urban development in the surrounding areas. To address this gap, the study analyses the socio-economic effects of improved connectivity, focusing on residential relocation trends, commuting patterns, housing market dynamics, and employment in smaller communities. Adopting a mixed-methods approach that integrates surveys with spatial modelling, the analysis examines changes in commuting habits, economic opportunities, and land use from 1990 to 2018 within a 45 min travel radius of the corridor. The findings reveal that enhanced accessibility has widened commuting ranges, stimulated urban growth, and transformed housing and labour markets. However, these advantages are not evenly distributed, highlighting emerging spatial disparities. By merging empirical data with predictive models, this study enriches the discourse on sustainable urban mobility and spatial equity, providing valuable insights for policymakers and planners as they contemplate future fixed-link transport connectivity aimed at fostering inclusive regional development.